Staying under the radar - the multifunctional LANA Protein - Custódio, Tânia Filipa Fernandes dos Santos Alves (2016)
Many viruses have developed numerous strategies to recruit and take advantage of cellular protein degradation pathways to evade the cellular viral immune system. One such virus is the Kaposi´s Sarcoma associated herpesvirus (KSHV), first discovered in Kaposi´s Sarcoma lesions found in AIDS patients. Latency-Associated Nuclear Antigen (LANA) is a KSHV multifunctional protein responsible for tethering viral DNA to the chromosome ensuring maintenance and segregation of the viral genome during cell division. Besides its main role of viral maintenance, LANA also physically interacts with several host proteins to modulate cell functions. One such function is to recruit the EC5S ubiquitin-ligase complex by interacting with Elongin BC complex and Cullin 5 protein, which in turn ubiquitinate substrates such as NF-κB and p53 to allow persistent viral infection. Like any other post-translation modifications, ubiquitination is reversible through deubiquitination enzymes (DUBs). LANA also interacts with ubiquitin specific protease 7 (USP7), a deubiquitination enzyme involved in regulation of several proteins including p53. Interaction with USP7 is made through a conserved peptide motif, which is also present in LANA. This work addresses the role of LANA in the recruitment and modulation of the ubiquitination and deubiquitination pathways. Despite the continued efforts in uncovering new LANA interacting partners to form a functional EC5S ubiquitin-ligase complex, only MHV-68 LANA interacted directly with Elongin BC, other interactions were not direct and may require a linker protein. On the other hand, LANA interaction with USP7 was able to be analysed by X-ray structure determination. In addition to a conserved P/AxxS motif, a novel Glutamine (Gln) residue from KSHV LANA was shown to make a specific interaction with USP7. This Gln residue is also present in other herpesvirus protein and hence it might be a conserved motif within herpesviruses.